Comparison of Secondary Anterior and Posterior Intraocular Lens Implantation for Aphakia - Uzma Fasih, Syed Shahid Asad, .Arshad Sheikh (Pakistan Journal of Ophthalmology, 2018)
Purpose: To study the visual outcomes and complications after secondary anterior and posterior intraocular lens implantation surgery in aphakic patients. Study Design: Study design was Quasi experimental type. Place and Duration of Study: Ophthalmology Dept. Abbasi Shaheed Hospital, Karachi from 30-7-2002 to 30-6-2003. Material and Methods: We selected 40 aphakic patient for secondary intraocular lens (IOL) implantation from the outpatient department. A proforma was filled pre and postoperatively. Patients were followed up for at least two months. The statistical data analysis was done on SPSS version 13. All Aphakic patients came to eye outpatient department were asked to participate in the study. Secondary intraocular lens implantation was done along with peripheral iridectomy, broad iridectomy, vitrectomy and corneal repair according to the requirement. Results: Eighteen (45%) patients were male and 22 (55%) patients were female. Patients were between 20 to 60 years of age. Thirty three (82.5%) patients had senile cataract while 7 (17.5%) patients had traumatic cataract. Most of traumatic cataract patient were below 30 years of age. Twenty seven (67.5%) patients had secondary Anterior chamber intraocular lens (AC IOL) and 13 (32.5%) patients had secondary posterior chamber intraocular lens (PC IOL) implantation done. Visual status after PC IOL implantation was better in 69.2%, remained same in 15.3% and decreased in 15.3% of patient while visual status after AC IOL improved in 62.9%, remained same in 25.9% and decreased in 11.11%. Vitrectomy was done in 15% of the patients who had AC IOL. There was increase in intraocular pressure which was controlled by medication. Three (7.5%) patients had vitritis while 2 (5%) patients had iris prolapse that was adequately managed. Conclusion: Secondary IOL implantation should be the procedure of choice and for the visual rehabilitation in aphakic patients. Key Words: Aphakia, Secondary intraocular lens implantation, Visual rehabilitation.